Unifikasi Kelompok Keagamaan Islam Berbasis Multi Interdisipliner Menuju Masyarakat Madani - Rohman, Abdul; Nurlaela, Nurlaela; Munasib, Munasib (Institute of Research and Public Service Universitas Jenderal Soedirman, 2023)
The purpose of this article is to reveal the problems of friction, conflict, and divisions that occur among Muslims, which are spread across several groups such as Nahdlatul Ulama, Muhammadyah, Jama'ah Islam, Tabligh Jama'ah, Salafi, and Ahmadiyah. In general, each group claims to be the appropriate group, so they are trapped in bigotry based on their group, doctrine, fatwa, or their leaders. The method of this study is library research in which the approach is carried out in a multi-disciplinary manner, namely through the science of interpretation, hadith, ushul fiqh, and sociology. The method of this study is based on library research in which the approach is carried out in a multi-disciplinary manner, namely through the science of interpretation, hadith, ushul fiqh, and sociology. The study's results found: 1) Islam highly upholds unity within the ummah. The prohibition of division has been imposed since the prophet's time before the Prophet Muhammad was revealed to the world. Therefore, the existence of religious groups should be to strengthen people and religion to try to avoid the perception of a single truth claim so as not to be trapped in the fanaticism of the group, schools of thought, fatwa, as well as towards their leaders; 2) Unification of religious groups can occur if it is based on intellectual awareness. This awareness can penetrate ideologies, schools of thought, and cultures. Without this awareness, unification is challenging to achieve; and 3) Intellectual awareness can be achieved through intellectual collaboration between religious group leaders. This intellectual awareness is a gateway to civil society, which has the characteristics of being open to knowledge, egalitarianism, and equality in the community, respecting human rights, respect for achievements, being highly civilized, and abandoning primordial attitudes.